Stephen Leacock: A Reappraisal - David Staines (Les Presses de l'Université d'Ottawa | University of Ottawa Press, 1986)
This collection of essays explores the many dimensions of the writings of Stephen Leacock, the well-loved Canadian author of Sunshine Sketches of a Little Town.